Crime Scene Photography in England, 1895–1960. (3rd January 2018) - Bell, Amy
Abstract: This article discusses the development of techniques and practices of murder crime scene photography through four pairs of photographs taken in England between 1904 and 1958 and examines their "forensic aesthetic": the visual combination of objective clues and of subjective aesthetic resonances. Crime scene photographs had legal status as evidence that had to be substantiated by a witness, and their purpose, as expressed in forensic textbooks and policing articles, was to provide a direct transfer of facts to the courtroom; yet their inferential visual nature made them allusive and evocative as well. Each of four pairs of photographs discussed reflects a significant period in the historical evolution of crime scene photography as well as an observable aesthetic influence: the earliest days of police photography and pictorialism; professionalization in the 1930s, documentary photography, and film noir; postwar photographic expansion to the suburban and middle class, advertising images of the family and home; and postwar elegiac landscape photography in the 1950s and compassion shown to infanticidal mothers. Crime scene photographs also demonstrate a remarkable shift in twentieth-century forensic technologies, and they reveal a collection of ordinary domestic and pastoral scenes at the moment when an act of violence made them extraordinary.